Emerging Encapsulation Technologies for Long-Term Reliability of Microfabricated Implantable Devices - Seung-Hee Ahn; Joonsoo Jeong; Sung June Kim (Micromachines, 2019)
The development of reliable long-term encapsulation technologies for implantable biomedical devices is of paramount importance for the safe and stable operation of implants in the body over a period of several decades. Conventional technologies based on titanium or ceramic packaging, however, are not suitable for encapsulating microfabricated devices due to their limited scalability, incompatibility with microfabrication processes, and difficulties with miniaturization. A variety of emerging materials have been proposed for encapsulation of microfabricated implants, including thin-film inorganic coatings of Al2O3, HfO2, SiO2, SiC, and diamond, as well as organic polymers of polyimide, parylene, liquid crystal polymer, silicone elastomer, SU-8, and cyclic olefin copolymer. While none of these materials have yet been proven to be as hermetic as conventional metal packages nor widely used in regulatory approved devices for chronic implantation, a number of studies have demonstrated promising outcomes on their long-term encapsulation performance through a multitude of fabrication and testing methodologies. The present review article aims to provide a comprehensive, up-to-date overview of the long-term encapsulation performance of these emerging materials with a specific focus on publications that have quantitatively estimated the lifetime of encapsulation technologies in aqueous environments.